Synthesis and assembly of SiO2-coated Bi2S3 nanofibers - Neves, Márcia C. (2003)
The SiO2 coating of Bi2S3 nanofibers using the alkaline hydrolysis of Si(OEt)4 is reported. A comparative study on the optical and morphological properties of the starting Bi2S3 nanofibers and the final SiO2 coated nanomaterials are presented and discussed. A SiO2 cap covering homogeneously single Bi2S3 nanofibers was obtained when the hydrolysis of Si(OEt)4 was performed under sonication treatment to maintain the fibers well separated during the coating process. These coated nanofibers were then used in a layer-by-layer deposition process to produce multilayered nanostructured films.